The didactics of vocational Bildung: how stories matter in VET research. (2nd July 2016) - Tyson, Ruhi
Abstract: In the research on education, the field roughly covered by the concept of Bildung has seen a wide-ranging discussion philosophically but less has been said and done from an empirical and vocational perspective. Bildung includes matters such as: formation of character, ethical and aesthetic knowledge/capability, capacity for wise deliberation and reflection as well as the development of personal autonomy. The focus here is on how narratives about teaching and curricula, both enacted and experienced, can be used to articulate significant aspects of Bildung-related practical knowledge. The empirical basis for this draws on a variety of narrative sources. By presenting, comparing and discussing narratives, it will be argued that there is a number of Bildung-related educational matters, not least in vocational education and training, where a narrative articulation can contribute. These can be differentiated in at least five groups: enriching knowledge of vocational tasks; conceptual development and critical reflection; advancement of practice; development of 'practice fields' and the articulation of patterns of vocational Bildung affordances. In distinguishing these different ways in which vocational Bildung as a form of practical knowledge can be enriched through narrative studies, the article contributes to our capacity for doing systematic research in the subject area.